DESCRIPTION OF LIES IN HOLY SOURCES AS NEGATIVE PERSONALITY QUALITIES (Conference Zone, 2022)
Modern man has many qualities, among which there are both deceit and lies. Unfortunately, many people do not understand the significance of some of their personality traits, which leads to various misunderstandings or even personal clashes. Naturally, each of us has faced many lies and deceit in our lives. Throughout life, each of us is deceived by someone or, on the contrary, deceived ourselves. Deception is based on the fact that a person uses a lie to protect himself if necessary